An Overview of the Self-Desires in the Light of Quranic Literature - Sumbal Ashraf; Saima Farooq (jihat-ul-islam, 2021)
A person who is inclined to fulfill his own desires will turn away from the path of Allah Almighty. Because the way of Allaah is a clear truth, in which success is contained. Whereas the self-desires are in contrary to the truth which are misleading and disgraceful and possess failure, the result of which is undoubtedly hell. The self desire is the worldly love, which is mortal, by being so inclined towards it; man ceases to account for his own self and surrounds a variety of meaningless aromas Which causes man to fall into sin and turn away from repentance. The Qur'an, which describes the worldly and the life in the hereafter with great clarity, if a person thinks about it, and then of course he will accept it psychologically and mentally. The love of this mortal world from his heart will not be to that extent because it will make sense of that fact that this world is just like a passageway. This concept does not create much hope in man, nor does he incline towards unconscious desires.